Possible Role of Vascular Risk Factors in Alzheimer's Disease and Vascular Dementia - Hasnain, Mehrul; Victor R Vieweg, W. . (Current Pharmaceutical Design, 2014)
The contribution of vascular risk factors to Alzheimer-vascular spectrum dementias is increasingly being recognized. We provide an overview of recent literature on this subject. Overweight and obesity as well as underweight during midlife predict cognitive decline and dementia later in life. Hypertension during midlife is also associated with dementia later in life and the association is stronger for untreated hypertension. Calcium channel blockers, angiotensin converting enzyme inhibitors, and angiotensin-1 receptor-blockers may be particularly beneficial in diminishing the risk of dementia associated with hypertension. Studies have fairly consistently shown that type 2 diabetes is a risk factor for dementia. Episodes of hypoglycemia add to this risk. Regular physical exercise during any point in the lifespan protects against cognitive decline and dementia. Most benefit is realized with physical exercise during early and midlife. Dyslipidemia also increases the risk of dementia but the findings are less consistent. Findings on the possible benefit of lipid-lowering agents (statins) are conflicting. Earlier studies identified smoking as protective of dementia but recent better designed studies have consistently shown that smoking increases the risk of dementia. The association of vascular risk factors with dementia is more robust for vascular dementia than Alzheimer’s disease. Heterogeneity of studies and lack of trials specifically designed to assess cognition as an endpoint make firm conclusions difficult. But considering the expected global burden of dementia and projected attributable risk of vascular risk factors to it, there is sufficient evidence to promote vascular risk factor reduction strategies as dementia prevention interventions.
Keywords: dyslipidemia